2017
DOI: 10.1038/onc.2016.472
|View full text |Cite|
|
Sign up to set email alerts
|

Unbalancing p53/Mdm2/IGF-1R axis by Mdm2 activation restrains the IGF-1-dependent invasive phenotype of skin melanoma

Abstract: Melanoma tumors usually retain wild-type p53; however, its tumor-suppressor activity is functionally disabled, most commonly through an inactivating interaction with mouse double-minute 2 homolog (Mdm2), indicating p53 release from this complex as a potential therapeutic approach. P53 and the tumor-promoter insulin-like growth factor type 1 receptor (IGF-1R) compete as substrates for the E3 ubiquitin ligase Mdm2, making their relative abundance intricately linked. Hence we investigated the effects of pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 63 publications
2
51
0
Order By: Relevance
“…By preventing the unregulated degradation of p53, nutlin-3 restores p53 levels in human melanoma cell lines, regardless of p53 mutational status (Ji et al, 2012;Worrall et al, 2017). However, nutlin-3 selectively decreases the viability of cells with wild-type p53 (Ji et al, 2012;Worrall et al, 2017). Interestingly, nutlin-3 treatment increases cellular levels of MDM2, resulting in ubiquitination and degradation of insulin-like growth factor type 1 receptor (IGF-1R) (Worrall et al, 2017).…”
Section: Protein/amino Acid Metabolism-arginine Proline and Protementioning
confidence: 99%
See 1 more Smart Citation
“…By preventing the unregulated degradation of p53, nutlin-3 restores p53 levels in human melanoma cell lines, regardless of p53 mutational status (Ji et al, 2012;Worrall et al, 2017). However, nutlin-3 selectively decreases the viability of cells with wild-type p53 (Ji et al, 2012;Worrall et al, 2017). Interestingly, nutlin-3 treatment increases cellular levels of MDM2, resulting in ubiquitination and degradation of insulin-like growth factor type 1 receptor (IGF-1R) (Worrall et al, 2017).…”
Section: Protein/amino Acid Metabolism-arginine Proline and Protementioning
confidence: 99%
“…However, nutlin-3 selectively decreases the viability of cells with wild-type p53 (Ji et al, 2012;Worrall et al, 2017). Interestingly, nutlin-3 treatment increases cellular levels of MDM2, resulting in ubiquitination and degradation of insulin-like growth factor type 1 receptor (IGF-1R) (Worrall et al, 2017). The disruption of the IGF-1R signaling axis causes an initial increase in melanoma cell proliferation but ultimately suppresses proliferation and inhibits migration (Worrall et al, 2017).…”
Section: Protein/amino Acid Metabolism-arginine Proline and Protementioning
confidence: 99%
“…Likewise, the IGF-1R could activate downstream non-kinase signaling pathways in a kinase-independent manner by employing the signal transduction machinery traditionally known to be used by the GPCR (e.g., the GRK/β-arrestin system and G-proteins) [32,33]. Equally important, components of these non-canonical, kinase-independent pathways orchestrate feedback mechanisms controlling the IGF-1R expression, trafficking, and signaling [34][35][36].…”
Section: Role Of Igf-1r Signaling In the Pathogenesis Of Dm And Cancermentioning
confidence: 99%
“…In particular, it has been suggested that fucoidan is able to enhance p21 expression at transcriptional level in a p53-independent manner (50). IGF-I signaling is strongly associated with cell growth and has a significant role in ribosome biogenesis by regulating the expression of proteins directly involved in the processing of ribosomal subunits and p53-mediated regulation of cell cycle progression (51). In particular, IGF-I activates the murine double minute 2 (MDM2) protein which is a component crucial regulator of cell proliferation and apoptosis and acts in association to some ribosomal proteins by inhibiting the p53 tumor suppressor (51).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-I signaling is strongly associated with cell growth and has a significant role in ribosome biogenesis by regulating the expression of proteins directly involved in the processing of ribosomal subunits and p53-mediated regulation of cell cycle progression (51). In particular, IGF-I activates the murine double minute 2 (MDM2) protein which is a component crucial regulator of cell proliferation and apoptosis and acts in association to some ribosomal proteins by inhibiting the p53 tumor suppressor (51). It has been demonstrated that fucoidan is able to synergize with standard anticancer agents as 5-FU and reduce its toxicity (52,53).…”
Section: Discussionmentioning
confidence: 99%